Cost-effectiveness of 3-months isoniazid and rifapentine compared to 9-months isoniazid for latent tuberculosis infection: a systematic review - Lai, Wendy A.; Brethour, Kaitlyn; D’Silva, Olivia; Chaisson, Richard E.; Zwerling, Alice A. (Université d'Ottawa | University of Ottawa, 2022)
Abstract Background We conducted a systematic review examining the cost effectiveness of a 3-month course of isoniazid and rifapentine, known as 3HP, given by directly observed treatment, compared to 9 months of isoniazid that is directly observed or self-administered, for latent tuberculosis infection. 3HP has shown to be effective in reducing progression to active tuberculosis and like other short-course regimens, has higher treatment completion rates compared to standard regimens such as 9 months of isoniazid. Decision makers would benefit from knowing if the higher up-front costs of rifapentine and of the human resources needed for directly observed treatment are worth the investment for improved outcomes. Methods We searched PubMed, Embase, CINAHL, LILACS, and Web of Science up to February 2022 with search concepts combining latent tuberculosis infection, directly observed treatment, and cost or cost-effectiveness. Studies included were in English or French, on human subjects, with latent tuberculosis infection, provided information on specified anti-tubercular therapy regimens, had a directly observed treatment arm, and described outcomes with some cost or economic data. We excluded posters and abstracts, treatment for multiple drug resistant tuberculosis, and combined testing and treatment strategies. We then restricted our findings to studies examining directly-observed 3HP for comparison. The primary outcome was the cost and cost-effectiveness of directly-observed 3HP. Results We identified 3 costing studies and 7 cost-effectiveness studies. The 3 costing studies compared directly-observed 3HP to directly-observed 9 months of isoniazid. Of the 7 cost-effectiveness studies, 4 were modelling studies based in high-income countries; one study was modelled on a high tuberculosis incidence population in the Canadian Arctic, using empiric costing data from that setting; and 2 studies were conducted in a low-income, high HIV-coinfection rate population. In five studies, directly-observed 3HP compared to self-administered isoniazid for 9 months in high-income countries, has incremental cost-effectiveness ratios that range from cost-saving to $5418 USD/QALY gained. While limited, existing evidence suggests 3HP may not be cost-effective in low-income, high HIV-coinfection settings. Conclusion Cost-effectiveness should continue to be assessed for programmatic planning and scale-up, and may vary depending on existing systems and local context, including prevalence rates and patient expectations and preferences.